National estimates of self-reported sitting time in adults with multiple sclerosis. Issue 1 (January 2018) - Sasaki, JE; Motl, RW; Cutter, G; Marrie, RA; Tyry, T; Salter, A
Background: Limited data exist on the prevalence and distribution of sedentary behavior (SB) in multiple sclerosis (MS). Objective: The objective of this paper is to describe sitting time as a metric of SB in a large national sample of people with MS. Methods: A total of 8004 individuals from the North American Research Committee on MS (NARCOMS) Registry completed the sitting time question from the International Physical Activity Questionnaire in spring 2015. We present descriptive data on sitting time for the total sample and across sociodemographic, clinical, and behavioral characteristics. Results: The final sample included 6483 individuals. Of these, 36.7% were classified with mild disability, 24.7% with moderate disability, and 38.6% with severe disability. Median sitting time for the total sample was 480 min/day (P25 = 310 min/day, P75 = 720 min/day). Sitting time was highest for individuals with MS who were male (540 min/day), not married (540 min/day), had a disease duration >30 years (540 min/day), were underweight (540.5 min/day), had an annual income of < 15, 000 (585 min/day), presented with a progressive form of MS (600 min/day), were classified as insufficiently active (600 min/day), or presented with severe disability (661 min/day). Conclusion: Sitting time is twice as high in individuals with MS compared to the general population (240 min/day).